Various space-time block codes over different modulation techniques using a new sphere decoder - Mishra, Priyanka; UL-Amin, Mehboob; K. Shukla, C (International Journal of Engineering and Technology, 2018)
In this paper, a detailed analysis based on the combination of spatial multiplexing and space time coding techniques under Rayleigh fading channel constraint in MIMO wireless communication systems is presented. The decoding algorithms of V-BLAST and Sphere Decoder are analyzed and their performance is evaluated using different Orthogonal Space-Time Block Codes techniques, with quasi and rotated quasi-orthogonal space-time block codes. The BER vs SNR curves of all the proposed algorithms have been verified for all modulation schemes including 64 QAM, 16QAM, QPSK and BPSK. A modified K and K1 Sphere decoder are proposed for the significant reduction of BER at higher modulation schemes. BER for 64 QAM modulation is calculated at optimum SNR of 20 dB and it has been shown, it gets significantly reduces when our proposed decoding algorithms are applied.Â